Comparative performance on plant morphology and biomass yield of two selected Moringa oleifera cultivars - Ahmed, S; Khan, MJ; Huque, KS; Sarker, NR; Habib, MA (Bangladesh Journal of Animal Science, 2020)
Moringa (Moringa oleifera) could be one of the promising tree fodders to meet up the seasonal forage shortage in Bangladesh. Two cultivars of Moringa oleifera species namely Black Seed Moringa (BSM-L) Local and White Seed Moringa (WSM-L) Local were cultivated at fodder research field in Bangladesh Livestock Research Institute (BLRI), Savar, Dhaka, Bangladesh during the period from August 2015 to December 2017 to determine plant morphology and biomass yield in different seasons of two consecutive years under common agronomical practices. The production performances of two Moringa cultivars were analyzed in an ANOVA of a Randomized Block Design (RBD). The result revealed that BSM-L had significantly higher survivability (89.12%, P<0.001), number of prune plant-1 (4.03, P<0.001) and lower defoliation rate (2.80%, P<0.04) than WSM-L(42.70%; 2.41 and 4.01%, respectively). On the other hand, leaf to stem ratio did not vary significantly (P<0.30) between cultivars (0.51 vs0.62). The annual fresh biomass yields (t ha-1) of BSM-L foliage (leaf+stem), stem and leaf (120.88, 84.14 and 45.07, respectively) were significantly (P<0.001) higher than that of WSM-L(33.71, 20.65and 12.67, respectively). On the other hand, the annual dry biomass yields (t ha-1) of BSM-L tops, stem and leaf (24.70, 14.49 and 09.85, respectively) were also significantly (P<0.001) higher than that of WSM-L (7.43, 3.93and 2.81, respectively). The seasonal effect of fresh foliage yield of Moringa showed that, dry& hot (March-June) (24.78 t ha-1/cut for BSM-L and 8.93 t ha-1/cut for WSM-L)and wet &hot(July-October) (31.48 t ha-1/cut for BSM-L and 6.85 t ha-1/cut for WSM-L)climates were found to be more suitable than dry & cool (November-February) (8.76 t ha-1/cut for BSM-L and 1.97 t ha-1/cut for WSM-L) climate. The initial growth of Moringa plants in the autumn or winter season was not satisfactory due to low temperature, humidity and rainfall. Results however, also showed that production of Moringa varied with variety and season. Finally, based on plant morphology and biomass yield, it may be concluded that, BSM-L may be cultivated as a potential tree fodder crop rather than WSM-L for ruminants in Bangladesh. Bang. J. Anim. Sci. 2020. 49 (1): 91-99